Soil bacterial diversity and community structure of Suaeda glauca vegetation in the Hetao Irrigation District, Inner Mongolia, China - Dong, Ruixiao; Wang, Xinbo; Li, Yuyi; Zhang, Hongyuan; Li, Xiaobin; Song, Jiashen; Chang, Fangdi; Feng, Wenhao; Pang, Huancheng; Wang, Jing (Frontiers in Microbiology, 2024)
Exploring the bacterial community in the S. glauca rhizosphere was of great value for understanding how this species adapted to the saline-alkali environment and for the rational development and use of saline-alkali soils. In this study, high-throughput sequencing technology was used to investigate the diversity characteristics and distribution patterns of soil bacterial communities in the rhizosphere of S.glaucadominated communities in the Hetao Irrigation Distract, Inner Mongolia, China. The relationships among bacterial characteristics, soil physicochemical properties and vegetation in four sampling sites were analysed. The soil bacterial communities in the rhizosphere of S. glauca-dominated communities were mainly composed of 16 phyla (i.e.,